ANALYSIS OF CRITERIA AND STRATEGIES USED FOR NOISE MONITORING AT AIRPORTS - Konovalova, Olena (Proceedings of National Aviation University (archive), 2015)
The paper gives an overview of international, national and local legislations and policies related to noise monitoring at airports via recommended criteria for measuring of noise levels generated during aircraft operations. The proposed classification of the criteria taking into accounts their characteristics and recommendations for application are described. Analysis of noise monitoring and mitigation strategies that have been identified as “best practice” is presented.